Respostas
respondido por:
1
f(x) = a x - 3
f( - 2 ) = - 2 a - 3 = 1 ----------> - 2 a = 1 + 3 --------> - 2 a = 4 ------> a = 4/-2 ---------> a = - 2. substituindo esse valor em f(x) = a x - 3, temos: f(x) = - 2 x - 3.
daí, f(1 ) é: f(x) = - 2 x - 3 --------> f(1) = - 2.1 - 3 ---------f(1 ) = - 2 - 3 = - 5
Resposta: f ( 1 ) = - 5
f( - 2 ) = - 2 a - 3 = 1 ----------> - 2 a = 1 + 3 --------> - 2 a = 4 ------> a = 4/-2 ---------> a = - 2. substituindo esse valor em f(x) = a x - 3, temos: f(x) = - 2 x - 3.
daí, f(1 ) é: f(x) = - 2 x - 3 --------> f(1) = - 2.1 - 3 ---------f(1 ) = - 2 - 3 = - 5
Resposta: f ( 1 ) = - 5
jaqueline167:
obg
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás